STUDY OF THE PHYSICAL-CHEMICAL PROPERTIES OF DRY LAND IN CHILI (Capsicum annum) GARDENS IN THE TARUNA JABALFARM FARMERS GROUP, NORTH CENTRAL TIMOR REGENCY - Maria Angelina Tuas; Natalia Desy Djata Ndua; Deseriana Bria; Bernadinus Bria Naifio (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Red chili (Capsicum annuum L.) is one of the most important vegetable commodities in the food industry and has many benefits. As a member of the Solanaceae family, red chili has high economic value and attractive market prospects. In addition to being consumed fresh as a mixture of cooking spices, chili fruit can also be preserved in various forms, such as pickles, sauces, chili flour, and dried fruit. This study aims to analyze the physical-chemical properties of soil in dry land used for chili cultivation (Capsicum annum L.) by the Taruna Jabalfarm Farmer Group in North Central Timor Regency. The parameters analyzed include soil texture, water content, organic matter, soil pH, and nutrient content such as nitrogen (N), phosphorus (P), and potassium (K). The results of the analysis showed that the soil has a sandy clay texture with a dominant sand content of 76.16%. The water content reaches 20.45%, organic matter is classified as low at 1.19%, slightly alkaline pH at 7.65%, and phosphorus content is very high at 62.26%, and potassium is quite good at 0.76%. Based on the results of this analysis, the soil requires additional processing in the form of organic matter and proper fertilization to support optimal growth of chili plants.